Profile of Speaking Activities of Senior High Schools (Teachers’ Experiences) - Sulastri Manurung (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2016)
This study aimed at describing the whole speaking activities in teaching learning English for Senior High Schools in Batam based on teachers’ experiences by giving an open questionnaire and then categorizing the data collected using continuous comparison technique. This research is a descriptive qualitative research with naturalistic approach. The research setting is in Batam. The key instrument of this research is the researcher herself. The data are gathered through distributing questionnaire. The data are in the form of words, phrases and sentences. The data gathered were selected based on the type of the activity, named the categories and broke the data into some categories which then would be shown in tables. The result of the research shows that speaking activities for senior high schools in Batam can be divided into six types in general then broke down into 19 categories. Speaking activity in monolog was the most frequently used by teachers and dominated the activity. It occurred 36 times in teaching and learning process.Keywords: profile, speaking, teachers’ experiences